Socio-economic status of fisherwomen community in coastal Vizianagaram district of Andhra Pradesh, India - Bhargavi, Kanchi; Chirwatkar, Bhogeshwar B.; Das, Anish; Behera, Samarendra; Bhakta, Dibakar (Journal of Fisheries, 2020)
The socio-economics of six fisherwomen co-operative societies in coastal Vizianagaram district of Andhra Pradesh were studied through field surveys by interviewing a total of 185 respondents. Respondents were mostly middle aged (31 – 56 years; 61.6%) living in nuclear families (64.9%). Majority of the fisherwomen were found illiterate (88.1%). A greater proportion (84.9%) of fisherwomen involved in fish marketing as a primary occupation followed by salting and curing (9.73%) and pickling of fishes (5.4%). More than half (56.2%) of the respondents earned > Rs. 25,000 (USD 1 = Rs. 75) every month. The study revealed that the socio-economic condition of the fisherwomen in the study area is poor, with a high percentage of the illiteracy. Necessary steps should be taken by the Governments organizations, NGOs and respective stakeholders to improve the literacy level as well as livelihood status.